Prevalence of Mental Health Illness among Patients with Adult-Onset Strabismus. (3rd July 2015) - Hassan, Mohamed B.; Hodge, David O.; Mohney, Brian G.
Abstract: Background : Children diagnosed with some forms of strabismus were recently found to have an increased risk of developing mental illness by early adulthood. The purpose of this case-controlled study was to determine if adults with non-paralytic forms of strabismus are similarly at an elevated risk for developing mental illness. Methods : The medical records of all patients diagnosed as adults (≥19 years of age) with convergence insufficiency (CI) ( n = 118), divergence insufficiency (DI) ( n = 80), and small angle hypertropia (HT ( n = 99) from January 1, 1985, through December 31, 2004, were retrospectively reviewed. Each case was compared with a sex- and birth date-matched non-strabismic control. The medical records were reviewed for mental health diagnoses, including inpatient and outpatient encounters, psychiatric ER visits, and medication use. Results : Mental health disorders were diagnosed in 65 (55.1%) patients with CI compared to 54 (45.8%) controls ( p = 0.15), in 51 (63.8%) patients with DI compared to 42 (52.5%) controls ( p = 0.15), and in 63 (63.6%) patients with HT compared to 57 (57.6%) controls ( p = 0.38). CI patients were not more likely to have mental health disorders than their controls ( p = 0.15). Mental health hospitalizations ( p = 0.02), psychiatric medication use ( p = 0.04), and unspecified anxiety disorders ( p = 0.03) were higher in DI patients compared to controls. HT patients were found to have more generalized anxiety disorders ( p = 0.003) than controls. Conclusions : Adults with some forms of strabismus (DI and HT) appear to have an increased risk of mental illness and its comorbidities, compared to age- and gender-matched non-strabismic controls.